2014
DOI: 10.1016/j.celrep.2014.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of the MiR-324-5p-CUEDC2 Axis Leads to Macrophage Dysfunction and Is Associated with Colon Cancer

Abstract: CUEDC2, a CUE-domain-containing protein, modulates inflammation, but its involvement in tumorigenesis is still poorly understood. Here, we report that CUEDC2 is a key regulator of macrophage function and critical for protection against colitis-associated tumorigenesis. CUEDC2 expression is dramatically upregulated during macrophage differentiation, and CUEDC2 deficiency results in excessive production of proinflammatory cytokines. The level of CUEDC2 in macrophages is modulated by miR- 324-5p. We find that Cue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 53 publications
0
54
1
Order By: Relevance
“…So, in our study we chose the littermate WT and CUEDC2 KO mice, avoiding the influence of other genetic factors. Although there was a report that CUEDC2 plays a role in protecting against colitis and maintaining intestinal length [3], our study demonstrated that colitis in CUEDC2 KO mice was much more severe than WT mice, showing the formation of larger and deeper ulcers, not limited to more ulcers as well as the worse diarrhea and bloody stool. The destruction of the function of the mucosal barrier in CUEDC2 KO mice was worsened, which in turn aggravated the inflammatory responses of colon.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…So, in our study we chose the littermate WT and CUEDC2 KO mice, avoiding the influence of other genetic factors. Although there was a report that CUEDC2 plays a role in protecting against colitis and maintaining intestinal length [3], our study demonstrated that colitis in CUEDC2 KO mice was much more severe than WT mice, showing the formation of larger and deeper ulcers, not limited to more ulcers as well as the worse diarrhea and bloody stool. The destruction of the function of the mucosal barrier in CUEDC2 KO mice was worsened, which in turn aggravated the inflammatory responses of colon.…”
Section: Discussioncontrasting
confidence: 72%
“…Sustained inflammatory reactions may also promote genomic instability. Therefore, since CUEDC2 inhibits inflammatory reactions in the colon, suppresses the activation of NF-jB and STAT3 pathways as well as the following expression of downstream anti-apoptotic genes, these mechanisms can explain the finding that CUEDC2 can inhibit the formation of colitis-associated cancer (CAC) [3]. These results suggest that CUEDC2 has the potential to become the clinical marker for the evaluation of colitis and CAC, however, which also need to be confirmed in clinical samples.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Of those upregulated, most are tumor supppressors and are involved in the disruption of cell migration and proliferation. These miRNAs have previously been implicated in cancers, namely miRNA 324-5p in hepatocellular carcinoma, breast cancer, and colon cancer [48–50], miRNA 935 in gastric signet ring cell carcinoma [51], and miRNA 15b-3p in prostate cancer [52]. More specifically, miRNA 16-5p has been found to block the proliferation and blood vessel formation of mesenchymal cells in women with PE [53].…”
Section: Discussionmentioning
confidence: 99%
“…The level of CUEDC2 in TAMs is downregulated by miR-324-5p, which in turn is upregulated by IL-4. Notably, CUEDC2 expression is almost undetectable in macrophages in human colon cancer, and this decreased CUEDC2 expression is associated with high levels of interleukin-4 and miR-324-5p [36]. Sonda et al showed that miR-142-3p downregulation enhanced macrophage M2-differentiation with immunosuppressive functions in tumor.…”
Section: Cancer To Macrophagesmentioning
confidence: 99%